Mathematical Model for Vehicle Routing and Scheduling with Forward and Reverse Logistics - Resti, Lady Ichwana; Mawengkang, Herman; Rosmaini, Elly (Politeknik Ganesha Medan, 2023)
Companies usually use cross-docking to reduce logistics costs. The product delivery process from suppliers to retailers and vice versa is facilitated by crossdocking facilities. One of important problem in crossdocking is vehicle routes. In this work we discuss about cross-docking problem for vehicle routes which is brought into the form of an integration model. We also present the strategy to handle the forward and reverse logistics. From this strategy we have a NP-hard mathematical model as the result.